Methods in Linguistics for Forming the Competent Approach to Similar Words (Eurasian Research Bulletin, 2023)
The field of linguistics encompasses a wide range of topics, one of which is the examination of imitation of words (idiomatic words) from a competency-based perspective, which is both extensive and scholarly in nature. This subject matter has significant relevance for anyone engaged in the study, research, composition, or instruction within the domain of linguistics, as it aids in the cultivation of the requisite proficiencies necessary for the acquisition and application of metaphors or linguistic methodologies.